2017
DOI: 10.1007/s11356-017-0226-5
|View full text |Cite
|
Sign up to set email alerts
|

Asthma disease as cause of admission to hospitals due to exposure to ambient oxidants in Mashhad, Iran

Abstract: Nowadays, asthma is one of the most common chronic respiratory diseases, worldwide. Many reports have emphasized the correlation between the short-term exposure to the ambient air pollutants and acute respiratory diseases, especially among children with asthmatic symptoms. The aim of this study was to evaluate the relationship between the exposure to three atmospheric antioxidants (NO, SO, and O) and hospital admission due to asthmatic disease (HAAD) in the city of Mashhad, Iran. The concentrations of atmosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…While the connection between CO, O 3 and risk of respiratory admission in children has been reported in previous studies (64)(65)(66)(67)(68), their effects on wheeze-associated disorders has not been proven among children in Southeast Asia (44)(45)(46)(47). In our review, there was no apparent association found for CO and O 3 , with a percent change of close to zero.…”
Section: Figure 2: (Continued)mentioning
confidence: 94%
“…While the connection between CO, O 3 and risk of respiratory admission in children has been reported in previous studies (64)(65)(66)(67)(68), their effects on wheeze-associated disorders has not been proven among children in Southeast Asia (44)(45)(46)(47). In our review, there was no apparent association found for CO and O 3 , with a percent change of close to zero.…”
Section: Figure 2: (Continued)mentioning
confidence: 94%
“…IE is rate of exposure for certain category of PM 2.5 concentration and BI, the baseline incidence rate of health endpoints. 41,42 The number of excess cases (NE) due to PM 2.5 exposure can be quantified if the target exposed population (N) is known as indicated in Eqs. (4).…”
Section: Ie = Ap × Bimentioning
confidence: 99%
“…O3 at ground level is an air pollutant because it is a strong oxidant that is highly reactive with tissues causing human health effects or producing harmful ecological and welfare effects, such as forest damage and reduced crop production. O3 has been associated with adverse effects on the respiratory system, cardiovascular diseases or even premature death (119,120). Acute exposure to air with high levels of O3 can trigger chest pain, coughs and wheezes, throat irritation, and airway inflammation.…”
Section: Ozone (O3)mentioning
confidence: 99%
“…Longer term exposure can reduce lung function and lung growth, lead to the development of asthma, and induce exacerbations of bronchitis, chronic obstructive pulmonary disease (COPD) and asthma (120). Increased ground level O3 has been associated with asthma and respiratory related exacerbations (69,119,(121)(122)(123)(124). Several European studies have reported that for each 10 µg/m 3 increase in O3 exposure, the daily mortality increases by 0.3% and occurrence of heart diseases increases by 0.4% (118).…”
Section: Ozone (O3)mentioning
confidence: 99%
See 1 more Smart Citation